Pengaruh Penerapan Metode Pelayanan Prima terhadap Kepuasan Penumpang Citilink di Bandar Udara International Juanda - Muh. Faliq Marselindo; Yulia Aji Puspitasari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Excellent service is the best service provided by the company in fulfilling consumer desires and expectations so that consumers feel satisfied. The consumers referred to here are passengers. Passenger satisfaction is a feeling where passengers' desires and hopes are achieved and even exceed their expectations. This research already implemented to determine the effect of implementing excellent service methods on Citilink passenger satisfaction at Juanda International Airport. Apart from that, this research also aims to find out how much influence the application of excellent service methods has on Citilink passenger satisfaction at Juanda International Airport. In this research, researchers used quantitative methods with the population of all Citilink airline passengers per month. In the sampling process the researcher used a purposive sampling method where the researcher took samples by determining certain qualifications, the number of samples was calculated using the Slovin formula and obtained results of 100 respondents, after the researcher collected the following data it would be analyzed using several analytical techniques such as instrument testing, hypothesis testing and testing coefficient of determination. The results of this research are that there is a positive influence between the application of excellent service methods on Citilink passenger satisfaction. This is known based on the conclusion of the T test, namely T count (5.328) is greater (>) than T table (1.984) with a significant value of 0.000 smaller (<) than 0.05, so it is assumed that the hypothesis is (H0) the null hypothesis is rejected and ( Ha) the alternative hypothesis is accepted, which means there is an influence of implementing excellent service on passenger satisfaction. To test the magnitude of the influence, it can be seen from the test results of the coefficient of determination R2, which is 87.9%.